Comparison of Different Invasive Devices for the Treatment of Urinary Incontinence after Radical Prostatectomy - Stefano Salciccia; Pietro Viscuso; Giulio Bevilacqua; Antonio Tufano; Paolo Casale; Ettore De Berardinis; Giovanni Battista Di Pierro; Susanna Cattarino; Alessandro Gentilucci; Francesca Lourdes Lia; Di Giulio Ivan; Davide Rosati; et al. (Advances in Urology)
Purpose. To compare different forms of invasive treatments for postradical prostatectomy (RP) urinary incontinence (UI) in terms of quantitative and qualitative parameters and continence recovery rate. Methods. We distinguished five categories of treatment: A = bulking agents, B = fixed slings, C = adjustable slings, D = circumferential compressor devices (artificial sphincter), and E = noncircumferential compressor devices (ProACT). A literature search was performed following the PRISMA guidelines. We performed a cumulative meta-analysis to explore the trend in the effect sizes across groups at postoperative follow-up. We compared the available treatment arms using standardized mean difference (SMD) and event rate (ER) for questionnaire results, number of pads/day, and percentage of pad-free patients. Evidence synthesis. 36 clinical trials were selected. At baseline, in the different populations, mean number of pad-day varied from 1.1 to 8.8, 24-hour pad weight varied extremely from 17.3 g to 747.0 g, and mean ICIQ-UI-SF questionnaire score varied from 4.8 to 18.6. Considering a random effect model among eligible studies, ER of continence recovery was 0.33 (95% CI −0.12–0.78), 0.63 (95% CI 0.55–0.71), 0.65 (95% CI 0.58–0.72), 0.50 (95% CI 0.34–0.66), and 0.53 (95%CI 0.36–0.70), respectively, in groups A, B, C, D, and E (I2 85.87%; Q 249.82—P>0.01) (test of group differences P=0.22). Conclusion. In our analysis, the use of adjustable and fixed slings is associated with the highest whereas the use of bulking agents is associated with the lowest recovery rate of continence after treatment. Results are conditioned by an elevated rate of heterogeneity in part explained with a high variability of consistence in urinary leakage at baseline among populations.